Pengaruh Pendekatan Humanistik Guru Terhadap Motivasi Intrinsik Belajar Sejarah Siswa di SMA Negeri 1 Cipongkor - Eriwan Pratama; Khaerul Syobar; Ernandia Pandikar (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
History learning in schools is often still teacher-centered, leading to passive student participation and low intrinsic motivation, this study investigates the effect of a humanistic teaching approach on students’ intrinsic motivation in learning history. A mixed methods approach with a sequential explanatory design was employed, in which quantitative data were collected and analyzed in the initial stage, followed by qualitative data to provide deeper explanations of the findings. The study was conducted at SMA Negeri 1 Cipongkor, involving 148 eleventh-grade students selected proportionally from a population of 235 students. Data were collected through Likert-scale questionnaires, supported by interviews, observations, and documentation. The findings indicate that the humanistic teaching approach has a positive and statistically significant effect on students’ intrinsic motivation. The analysis shows a moderate positive relationship, indicating that improvements in the implementation of humanistic teaching are associated with increased levels of students’ intrinsic motivation. Furthermore, the results demonstrate that the humanistic approach contributes meaningfully to students’ motivation, although other factors beyond this study also play a role. Qualitative findings further reveal that students are more motivated when teachers demonstrate empathy, provide autonomy, and create supportive and interactive learning environments. In conclusion, the humanistic teaching approach plays an important role in enhancing students’ intrinsic motivation in learning history. However, other contributing factors should also be considered, highlighting the need to integrate humanistic principles with other instructional strategies.